Odpowiedź :
Odpowiedź:
a)
4x - 3 = 3x + 5
4x - 3x = 5 + 3
x = 8
b)
5x + 2 = 7 - 3x
5x + 3x = 7 - 2
8x = 5 |:8
x = 8/5
x = 1 i 3/5
c)
3 (x - 1) = 0
3x - 3 = 0 |+3
3x = 3 |:3
x = 1
d)
-6 (x + 1) = 24
-6x - 6 = 24 |+6
-6x = 30 |:(-6)
x = -5
e)
-7 (x - 2) = 3x - 1
-7x + 14 = 3x - 1
-7x - 3x = -1 -14
-10x = -15 |:(-10)
x = 1,5
f)
4 (x - 1) = 6 (1 + x)
4x - 4 = 6 + 6x
4x - 6x = 6 + 4
-2x = 10 |:(-2)
x = -5
Szczegółowe wyjaśnienie:
Odpowiedź:
a)4x-3=3x+5 (przerzućmy na jedną strone "x")
x=8
b)5x+2=7-3x (przerzućmy na jedną strone "x")
8x=9 /:8
x=1[tex]\frac{1}{8}[/tex]
c)3(x-1)=0
3x-3=0
3x=3 /:3
x=1
d) -6(x+1)=24
-6x-6=24
-6x=30 /:(-6)
x=-5
e)-7(x-2)=3x-1
-7x+14=3x-1 (przerzućmy na jedną strone "x")
-10x=-15 /:(-10)
x=1,5
f)4(x-1)=6(1+x)
4x-4=6+6x (przerzućmy na jedną strone "x")
-10=2x /:2
-5=x